UPAYA PENINGKATAN KINERJA GURU MELALUI PENDEKATAN INDIVIDUAL BERBANTUAN SUPERVISI AKADEMIK DI SD NEGERI 1 NGLAYANG KECAMATAN JENANGAN KABUPATEN PONOROGO - Wahyudi - Wahyudi (Universitas PGRI Madiun); Nurhadji - Nugraha (Universitas PGRI Madiun); Sudarmiani Sudarmiani (Universitas PGRI Madiun) (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
This study aims to determine efforts to improve teacher performance through an individual approach assisted by academic supervision in SD Negeri 1 Nglayang, Jenang District, Ponorogo Regency.This research use desciptive qualitative approach. While this type of research uses School Action Research. School Action Research  is a type of research conducted by principals and school supervisors. This school action research was carried out in a collaborative and participatory way, that is, researchers did not conduct their own research, but collaborated (in collaboration) with teachers in SD Negeri 1 Nglayang, Jenang District, Ponorogo Regency.The results showed that: 1) The implementation of academic supervision, obtained good results because there was an increase in results in the second cycle compared to the first cycle; 2) Teacher performance in SD Negeri 1 Nglayang; (a) professional aspects, (b) pedagogical aspects, and (c) social aspects very good results; 3 Implementation of academic supervision can improve teacher performance through individual teacher approaches at SD Negeri 1 Nglayang Jenang District Ponorogo District, this can be seen from: (a) Educational supervision that has been carried out for the professional aspect; (b) Educational supervision that has been carried out for pedagogical aspects; (c) Educational supervision that has been carried out for social aspects has been successful. Keywords: Teacher Performance, Individual Approach, Academic Supervision